IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Tuti Kurnia; Novia Lisliningsih, Deni Irawati, Wedra Aprison (CV. ADIBA AISHA AMIRA, 2023)
The government's policy to replace the 2013 curriculum with an independent learning curricular has influenced paradigm changes as well as the goal of learning generally included in the learning of Islamic religion. The method of research used in this article is by using library methods, i.e. reading various journals and books, collecting literature and storing it on other sources of information in the library to gain a good and correct understanding of the implementation of the Merdeka curriculum in the teaching of Islamic religion